Laparoscopic resection of a giant pelvic solitary fibrous tumor: a case report - Shi, Zhoulei; Yan, Shuaijiang; Yu, Chunhong; Guo, Liuxiong; Zhang, Panying; Cui, Jiarui; Li, Shoubin (Frontiers in Oncology, 2025)
ObjectiveTo improve the understanding, diagnosis, and treatment of giant pelvic solitary fibrous tumor (SFT).MethodsWe report a case of a giant pelvic SFT treated in our hospital. The clinical features, pathological findings, and treatment approach are described, and the current status of diagnosis, treatment, and prognosis is discussed with reference to the literature.ResultsA 69-year-old male patient was admitted due to progressive dysuria for over 6 months and was diagnosed with a pelvic SFT. The patient underwent laparoscopic resection of the pelvic SFT. Postoperative pathological examination revealed a spindle cell tumor, consistent with a solitary fibrous tumor based on immunohistochemical staining. The patient recovered well postoperatively and remains under close follow-up.ConclusionPelvic SFT are clinically rare and exhibit unique pathological characteristics. Compared to traditional open surgery, this case demonstrates that laparoscopic surgery may be a superior option for large pelvic masses.